Tokyo vice : an American reporter on the police beat in Japan - Adelstein, Jake (Pantheon Books, 2009)
From the only American journalist ever to have been admitted to the insular Tokyo Metropolitan Police press club: a unique, firsthand, revelatory look at Japanese culture from the underbelly up. For twelve years of eighty-hour workweeks, he covered the seedy side of Japan--extortion, murder, human trafficking, and corruption. Here, he tells the riveting, often humorous tale of his journey from an inexperienced cub reporter to a daring investigative journalist with a yakuza price on his head. With its visceral descriptions of crime in Japan and an exploration of the world of modern-day yakuza that even few Japanese ever see, this is a fascination, and an education.--From publisher description.